Computing total edge irregularity strength of some n-uniform cactus chain graphs and related chain graphs - Isnaini Rosyida; Diari Indriati (Indonesian Combinatorial Society (InaCombS), 2020)
Given graph G(V,E). We use the notion of total k-labeling which is edge irregular. The notion of total edge irregularity strength (tes) of graph G means the minimum integer k used in the edge irregular total k-labeling of G. A cactus graph G is a connected graph where no edge lies in more than one cycle. A cactus graph consisting of some blocks where each block is cycle Cn with same size n is named an n-uniform cactus graph. If each cycle of the cactus graph has no more than two cut-vertices and each cut-vertex is shared by exactly two cycles, then G is called n-uniform cactus chain graph. In this paper, we determine tes of n-uniform cactus chain graphs C(Cnr) of length r for some n ≡ 0 mod 3. We also investigate tes of related chain graphs, i.e. tadpole chain graphs Tr(4,n) and Tr(5,n) of length r. Our results are as follows: tes(C(Cnr)) = ⌈(nr + 2)/3⌉ ; tes(Tr(4,n)) = ⌈((5+n)r+2)/3⌉ ; tes(Tr(5,n)) = ⌈((5+n)r+2)/3⌉.